2017
DOI: 10.1182/blood-2017-06-788323
|View full text |Cite
|
Sign up to set email alerts
|

Promising efficacy and acceptable safety of venetoclax plus bortezomib and dexamethasone in relapsed/refractory MM

Abstract: Key Points• In relapsed/refractory MM, venetoclax plus bortezomib and dexamethasone appears to be safe and efficacious.• This is a novel therapeutic approach for MM.The antiapoptotic proteins BCL-2 and myeloid cell leukemia sequence 1 (MCL-1) promote multiple myeloma (MM) cell survival. Venetoclax is a selective, orally bioavailable smallmolecule BCL-2 inhibitor; bortezomib can indirectly inhibit MCL-1. In preclinical studies, venetoclax enhanced bortezomib activity, suggesting that cotargeting of BCL-2 and MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
174
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(185 citation statements)
references
References 32 publications
7
174
2
2
Order By: Relevance
“…28 Accordingly, an ongoing phase 1b study of venetoclax in combination with bortezomib and dexamethasone (NCT01794507) has shown high response rates in patients with relapsed/refractory MM irrespective of t (11;14) status. 29 In the present study, the addition of dexamethasone at the time of progression did not appear to add any clinical benefit for patients on venetoclax monotherapy.…”
Section: Discussioncontrasting
confidence: 51%
“…28 Accordingly, an ongoing phase 1b study of venetoclax in combination with bortezomib and dexamethasone (NCT01794507) has shown high response rates in patients with relapsed/refractory MM irrespective of t (11;14) status. 29 In the present study, the addition of dexamethasone at the time of progression did not appear to add any clinical benefit for patients on venetoclax monotherapy.…”
Section: Discussioncontrasting
confidence: 51%
“…Based on this strong mechanistic rationale and a strong preclinical data package, a phase 1 study investigating the combination of venetoclax with bortezomib and dexamethasone was initiated. Preliminary results have shown an acceptable safety profile and promising responses, particularly in patients naïve or sensitive to prior bortezomib therapy (78). Synergistic effects with BCL-2 antagonists have also been explored with histone deacetylase and insulin-like growth factor-1 inhibitors as potential therapeutic options for patients with MM (7981).…”
Section: Identifying Sensitive Tumor Types and Likely Respondersmentioning
confidence: 99%
“…Moreover, for those patients not refractory to proteasome inhibitors and immunomodulatory agents, the response rate for the triple combination reached an impressive 92%. Overall response rates were similar across different cytogenetic profiles; most notably it was 47% in those patients [15] who had deletion 17p, a particularly high-risk subgroup with severely compromised apoptosis process. The importance of high BCL-2 expression predicting better and more prolonged clinical response was also underlined in this study.…”
Section: Introductionmentioning
confidence: 71%
“…It was also shown that dexamethason sensitizes myeloma cell lines and primary myeloma cells to venetoclax activity, therefore clinical study M12-901 was initiated to test this triple combination (bortezomib-venetoclaxdexamethason) in relapsed/refractory myeloma patients [15]. Here, the objective response level reached 67% and was not restricted at all to t(11;14) patients, proving the validity of the approach.…”
Section: Introductionmentioning
confidence: 99%